Potential Wetland habitats of Schirmacher Oasis, Antarctica: Wetland habitat, antarctica - Dhargalkar, Vinod (IJRDO-Journal of Applied Science, 2020)
Abstract Biologically, phytoplankton and benthic algae dominates most lakes of the Schirmacher Oasis that experience large seasonal variations in their populations. The bulk of the biomass and primary productivity is contributed by cyanobacteria, diatoms, and green algae, which form thick luxuriant mats several meters thick. Benthic algae, foundation species regulate many of the processes that characterize wetland ecosystems by controlling dissolved oxygen concentrations, sediment formation, nutrient uptake and retention and account for a significant amount of total primary production. In this review, an overview on which foundation species define the structural features and ecosystem functioning of representative freshwater wetlands and how they influence and respond to hydrology, nutrient and habitat dynamics have been assessed.